Anxiety and Insomnia Among Urban Slum Dwellers in Bangladesh: The Role of COVID-19 and Its Associated Factors - Koly, Kamrun Nahar; Khanam, Mosammat Ivylata; Islam, Md. Saiful; Mahmood, Shehrin Shaila; Hanifi, Syed Manzoor Ahmed; Reidpath, Daniel D.; Khatun, Fatema; Rasheed, Sabrina (Frontiers in Psychiatry, 2021)
Background: Although mental health is an important part of health and well-being, very little is known about the impact of COVID-19 pandemic on the mental health of marginalized communities like urban slum dwellers. Our study estimated the prevalence of generalized anxiety disorder and insomnia among the residents of the informal settlements of Dhaka, Bangladesh during the COVID-19 pandemic. Methods: A cross-sectional phone-based survey was conducted from October-November 2020 among adult residents of five informal settlements of Dhaka city randomly chosen from an existing Urban Health and Demographic Surveillance Systems (UHDSS) run by icddr,b. Data on Generalized Anxiety Disorder-7 (GAD-7) and Insomnia Severity Index (ISI) were collected. A multinomial logistic regression was performed to assess the associated factors of anxiety and insomnia. Results: Of the total 586 participants, the prevalence of mild to severe anxiety and insomnia were 53% and 43%, respectively. As per as the multinomial regression analysis, participants with mild anxiety were significantly more likely to be older (> 50 years), and afraid of COVID-19 infection. Likewise, participants with moderate/severe anxiety were significantly more likely to share less household facilities (e.g., toilet, kitchen, water) (OR: 2.23; 95% CI: 1.31-3.79), to have difficulties in food availability (OR: 2.76; 95% CI: 1.10-6.93), afraid of self (OR: 5.27; 95% CI: 2.82-9.88) and family members (OR: 2.26; 95% CI: 1.23-4.17) to be infected. Participants with mild insomnia were significantly more likely to share fewer household facilities, and be afraid of being infected with COVID-19 infection. Moreover, participants with moderate/severe insomnia were significantly more likely to be female (OR: 1.90; 95% CI: 1.02-3.56), to receive food aid (OR: 0.50; 95% CI: 0.29-0.88), to be afraid of self (OR: 3.85; 95% CI: 1.81-8.19) and someone like friends or neighbors (OR: 2.45; 95% CI: 1.07-5.58) get infected with COVID-19. Conclusions: We found elevated prevalence of both anxiety and insomnia among the urban poor of Bangladesh in the context of COVID-19. This indicates the importance of integrating mental health in the mitigation and recovery efforts related to similar crises for the urban poor in the future.